Pros and Cons of 19 Sport-Related Concussion Educational Resources in Canada: Avenues for Better Care and Prevention - Cusimano, Michael D.; Zhang, Stanley; Topolovec-Vranic, Jane; Grosso, Ashley; Jing, Rowan; Ilie, Gabriela (Frontiers in Neurology, 2018)
Introduction: While progress is occurring regarding the diagnosis and treatment of concussion, more work is required on how to translate new knowledge about concussion to stakeholders. The purpose of the present study was to identify the organizations who should deliver sports-related concussion information, the best methods for delivery, and factors affecting the accessibility and usability of the resources for knowledge translation (KTR). Methods: Nationwide electronic survey of the Canadian sports community regarding concussion and knowledge translation. Results: A total of 12168 usable responses were obtained. National or provincial sports organizations, coaches and trainers, federal and provincial governments were identified as the top five groups who should deliver concussion information regardless of the respondent’s age or community role. Among the information delivery options, YouTube videos and TV segments were most selected. Social media were more popular among younger respondents whereas brochures were more popular among those over 35 years of age. Usability and accessibility of KTR varied widely. Regression analyses showed that sex and community/social role of the respondents affected respondents’ rating of the accessibility and usability. Conclusion: Sports organizations, schools, and, governments should play larger roles in the delivery of concussion information through teams, leagues, school physical education class, TV, online or social media, brochures, or coaches/trainers. Respondents’ ratings of the accessibility and usability of the various concussion KTR will provide useful information for both the KTR developers and users.